2018
DOI: 10.1111/jog.13680
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of resveratrol in improving ovarian function in a rat model of premature ovarian insufficiency

Abstract: Resveratrol reduced oxidative stress and inhibited apoptosis in granulosa cells by activating the PI3K/Akt/mTOR signaling pathway in a rat model of POI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 12 publications
1
39
0
Order By: Relevance
“…We found that CD4 + CD25 + Tregs partially rescued the effects of pZP3 via multiple mechanisms, including inhibition of the apoptosis conditions in the ovaries, regulation of the secretion of hormones and follicle development, as described in other reports (Li & Liu, 2018;Ling et al, 2019;Zhang et al, 2019). Data also showed that CD4 + CD25 + Tregs significantly decreased Akt and FOXO3a expression in ovarian tissues.…”
supporting
confidence: 82%
“…We found that CD4 + CD25 + Tregs partially rescued the effects of pZP3 via multiple mechanisms, including inhibition of the apoptosis conditions in the ovaries, regulation of the secretion of hormones and follicle development, as described in other reports (Li & Liu, 2018;Ling et al, 2019;Zhang et al, 2019). Data also showed that CD4 + CD25 + Tregs significantly decreased Akt and FOXO3a expression in ovarian tissues.…”
supporting
confidence: 82%
“…24,25 In a rat POI model induced by chemotherapy or radiotherapy, resveratrol inhibited oxidative stress and inflammatory events in ovaries by activating the PI3K/Akt/mTOR and NF-κB signaling pathways. [26][27][28] Resveratrol also improved loss of the oogonial stem cells through antiapoptotic effects in POI model mice. 29 Therefore, resveratrol may help as a therapeutic POI supplement; however, this has not yet been proven in human studies.…”
Section: Primary Ovarian Insufficiency (Poi)mentioning
confidence: 91%
“…During oocyte maturation and folliculogenesis, the phosphatidylinositol‐4,5‐bisphosphate 3 kinase (PI3K)/protein kinase B (Akt)/mammalian target of rapamycin (mTOR) and nuclear factor‐κ light‐chain enhancer of activated B cell (NF‐κB) signaling pathway play roles in the development of primordial follicles and oocytes and in the proliferation and differentiation of granulosa cells . In a rat POI model induced by chemotherapy or radiotherapy, resveratrol inhibited oxidative stress and inflammatory events in ovaries by activating the PI3K/Akt/mTOR and NF‐κB signaling pathways . Resveratrol also improved loss of the oogonial stem cells through antiapoptotic effects in POI model mice .…”
Section: Impact On Ovary For Pregnancymentioning
confidence: 99%
“…These findings stay in accordance with results of Bazerra et al, reporting that resveratrol enhances primordial follicle activation and decreases the level of DNA fragmentation in in vitro cultures of ovine ovarian tissue. Furthermore, they have also shown the ability of resveratrol to stimulate GCs proliferation via activation of the PI3K pathway [ 44 , 97 ]. PI3K is known as one of the fundamental signaling pathways, involved in follicle activation in rodents [ 44 ].…”
Section: The Modulation Of Granulosa Cell Physiological Processes mentioning
confidence: 99%
“…PI3K/Akt/mTOR signaling pathway is known to play a key role in the oocyte growth, as well as proliferation and differentiation of GCs. Accordingly, resveratrol has been reported to reduce oxidative stress in rat model of premature ovarian insufficiency by inducing the expression of factors involved in PI3K/Akt/mTOR pathway activation [ 97 ].…”
Section: The Modulation Of Granulosa Cell Physiological Processes mentioning
confidence: 99%